Effect of 2009 Drought on Household Livelihoods in Laikipia West Sub-County, Kenya - Karanja, Amon; Ondimu, Kennedy; Recha, Charles (Annals of Arid Zone, 2018)
Prolonged and severe drought has affected many parts of sub-Saharan Africa, resulting in increased cases of disease, hunger and destruction of habitats. This study assessed effects of drought on household livelihoods in Laikipia West sub-County in Kenya through a survey and in-depth interview. The study utilized household surveys (N=180) and Key Informant Interview (N=8) data and descriptive data analyses tools were used for data analyses. The 2009 drought led to reduced crop yields (32.5%) and crop failure (12.6%). With respect to cropped area and livestock, 26% of the respondent reported that about 75% of their crop area was impacted by drought while 78% of respondents reported few livestock death during the drought. The study recommends enhanced social programs to support households when they suffer losses due to drought as a coping mechanism. Policy on compensation by the Ministry of Environment and Natural resources and the county government of Laikipia will enable the affected households meet their basic needs just like those who are able to harvest crops.Key words: Severe drought, drought impact, household livelihood, enhanced compensation